Seismic performance and strengthening of traditional masonry buildings in the city centre of Coimbra - Vicente, R. (2006)
The increasing concern and consequent appraisal on durability, conservation state and changeable use and function of old buildings in urban centres relies a great deal on the structural safety evaluation of vertical load capacity but also the capable resistance to horizontal forces. The need to assess seismic vulnerability, particularly of the traditional masonry buildings is a key issue. Particular attention has been put upon the building stock of the old city centre of Coimbra, mainly constituted by old masonry load-bearing buildings of significant architectural value. The evaluation of the seismic vulnerability of old buildings is essential in the definition of the strengthening needs and minimization of possible damages due to seismic actions, in safeguarding of built heritage or in the identification of critical buildings. This paper intends to contribute for the assessment of old buildings considering the local seismic risk. A three dimensional model was developed for an aggregate of four buildings. The finite element modelling of these buildings has intended to identify structural fragilities, help understand the damages detected in the existing structures (crack opening) and evaluate the global structural safety of this type of buildings. It will be presented the main results obtained in this study, interpreted the structural damage, stress distribution and verified the global stability and its consequences. The dynamic response of such constructions to seismic actions has allowed studying the structural vulnerability. Different strengthening techniques to improve the global behaviour of these buildings were modelled and analysed. Efficiency comparison of the strengthening strategies is also discussed.